OPTIMIZATION OF MATERIAL COMPOSITION FOR THE SYNTHESIS OF UREA FORMALDEHYDE (UF) RESIN MODIFIED BY POLYVINYL ALCOHOL (PVA) - Thi Thuan, Nguyen; Manh Truong, Vu; Van Tu, Nguyen (Journal of Forestry Science and Technology, 2022)
Polyvinyl alcohol (PVA) was added to the synthesis of urea formaldehyde (UF) resin to reduce free formaldehyde (F) content, improve resin quality. The PVA-modified UF resin was synthesized in the laboratory. This modified resin was used as an adhesive for the production of plywood. Response surface methodology (RMS) was applied to optimize the amount of PVA addition and the molar ratio in the first stage of reaction process (F/U1) based on the quality criteria of the resin, including: solid content, curing time, water solubility, free formaldehyde (F) content and tensile shear strength, modulus of rupture, modulus of elasticity of plywood using modified resin to producing. The experiment was set with central composite design (CCD) for investigating the effects of the amount of PVA addition (1 – 3%) and molar ratio of F/U1 (1.8 – 2.0) on selected criteria. The results showed that the modified resin was optimal when using the amount of PVA = 1.6% of the total amount of urea and molar ratio of F/U1 = 1.91. The quality criteria achieved: solid content, curing time, water solubility, free formaldehyde content of the resin were 54.1%; 84 seconds; 3.2 times; 0.62%, respectively and tensile shear strength, modulus of rupture (MOR), modulus of elasticity (MOE) of the plywood were 2.09 MPa; 55.7 MPa; 9.1 GPa, respectively.